STRATEGI PENINGKATAN PRODUKSI DAN EKSPOR JAGUNG DI PROVINSI LAMPUNG / Strategy to Improve Corn Production and Export in Lampung Province - Yulia Pujiharti; Ratna Wylis Arief (Jurnal Penelitian dan Pengembangan Pertanian, 2021)
The population of Lampung continues to increase and the rapid development of the industry causes the need for maize in this area to continue to increase as well. This paper provides alternative steps to increase the production and export of maize in Lampung Province. Maize production can be increased by increasing the harvest area by expanding the planted area to suboptimal untapped land, such as in Mesuji, Pesisir Barat, and West Lampung districts. Another effort that can be made to increase maize production is to apply an intercropping pattern on the same land. Another strategy is to increase productivity by using hybrid maize such as varieties NK-22, P-21, and Bisi-2, providing manure, balanced fertilizers, integrated pest and disease management (IPM), and application of post-harvest technology. Efforts to increase harvested area and productivity need to be continued to increase corn production sustainably. The strategy to increase exports is to increase production and reduce the need for corn for feed and other uses (other than foodstuffs). In this case, the corn that will be used for feed and other uses can be replaced by sorghum.Keywords: Corn, production, export, strategy AbstrakJumlah penduduk Lampung yang terus meningkat dan perkembangan industri yang pesat menyebabkan kebutuhan jagung di daerah ini terus pula meningkat. Tulisan ini memberikan alternatif langkah-langkah peningkatan produksi dan ekspor jagung di Provinsi Lampung. Produksi jagung dapat ditingkatkan melalui penambahan luas panen dengan memperluas areal tanam ke lahan suboptimal yang belum dimanfaatkan, seperti di Kabupaten Mesuji, Pesisir Barat, dan Lampung Barat. Upaya lain yang dapat dilakukan untuk meningkatkan produksi jagung adalah menerapkan pola tumpangsari pada lahan yang sama. Strategi lainnya yaitu meningkatkan produktivitas dengan penggunaan jagung hibrida seperti varietas NK-22, P-21, dan Bisi-2, pemberian pupuk kandang, pupuk berimbang, pengelolaan hama dan penyakit secara terpadu (PHT), dan penerapan teknologi pascapanen. Upaya peningkatan luas panen dan produktivitas perlu diteruskan agar produksi jagung meningkat secara berkelanjutan. Strategi peningkatan ekspor yaitu dengan meningkatkan produksi dan mengurangi kebutuhan jagung untuk pakan dan penggunaan lain (selain bahan makanan). Dalam hal ini, jagung yang akan digunakan untuk pakan dan penggunaan lain dapat digantikan oleh sorgum.Kata kunci: Jagung, produksi, ekspor, strategi